Unveiling FOXO3's metabolic contribution to menopause and Alzheimer's disease - Christopher O'Mahony; Oscar Hidalgo-Lanussa; George E. Barreto (Experimental Gerontology)
The increasing prevalence of Alzheimer's disease (AD) calls for a comprehensive exploration of its complex etiology, with a focus on sex-specific vulnerability, particularly the heightened susceptibility observed in postmenopausal women. Neurometabolic alterations during the endocrine transition emerge as early indicators of AD pathology, including reduced glucose metabolism and increased amyloid-beta (Aβ) deposition. The fluctuating endocrine environment, marked by declining estradiol levels and reduced estrogen receptor beta (ERβ) activity, further exacerbates this process. In this context, here we explore the potential of forkhead box O3 (FOXO3) as a critical mediator linking metabolic disturbances to hormonal decline. We propose that FOXO3 plays a key role in the intersection of menopause and AD, given its dysregulation in both AD patients and postmenopausal women, modulating cellular metabolism through interactions with the AMPK/AKT/PI3K pathways. This relationship highlights the intersection between hormonal changes and increased AD susceptibility. This review aims to open a discussion on FOXO3's contribution to the metabolic dysregulation seen in menopause and its impact on the progression of AD. Understanding the functional role of FOXO3 in menopause-associated metabolic changes could lead to targeted therapeutic strategies, offering novel insights for managing for this condition.